Hubungan Antara Forgiveness Dengan Psychologial Well- Being Pada Remaja Korban Perceraian di Kota Bekasi - E, Erlangga; Supriatna, Ecep (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the relationship between forgiveness and psychological well-being in adolescent victims of divorce. This research uses quantitative methods with a correlational study type. The sample of this study amounted to 202 respondents with sampling using the Popusive sampling technique. The measuring instruments used in this study are forgiveness and psychological well-being scales. The results of this study indicate that there is a relationship between forgiveness and psychological well-being in adolescent victims of divorce. Suggestions for future researchers to use a longitudinal approach to understand changes in the relationship between forgiveness and psychological well-being over time. This is important because the relationship between the two variables can be dynamic, influenced. In addition, a mixed-method approach that combines quantitative and qualitative data can provide a more holistic understanding. Research instruments also need to be developed to be more valid and reliable, taking into account context. The use of multilevel analysis is also recommended to look at interactions between levels.